2018
DOI: 10.1002/pola.29254
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Carbazole‐Based Schiff Bases as Photoinitiators: From Facile Synthesis to Efficient Two‐Photon Polymerization

Abstract: Exploration of simple and economical synthetic routes to construct active two-photon initiators (2PIs) with long conjugation length is highly desirable to promote the development of two-photon-induced photopolymerization technology. In this article, several conjugated carbazole-based derivatives containing N=C bonds as π bridges and electron donor/acceptor groups were prepared through one-step Schiff base reaction. The structure-activity relationship was systematically investigated through calculations and exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…Currently two‐photon 3D printing has been mainly limited to academic research due to its low printing speed . To promote two‐photon 3D printing into the market, development of efficient two‐photon initiators (2PIs), a key compound in photoactive formulations, is highly desirable to guarantee fast printing rates, a reduced polymerization threshold, and finally fabricated structures with a high resolution . An efficient 2PI should have large two‐photon absorption (2PA) to ensure efficient photon absorption, and an efficient initiation mechanism, through which the absorbed energy can be efficiently used to generate active initiation species .…”
Section: Methodsmentioning
confidence: 99%
“…Currently two‐photon 3D printing has been mainly limited to academic research due to its low printing speed . To promote two‐photon 3D printing into the market, development of efficient two‐photon initiators (2PIs), a key compound in photoactive formulations, is highly desirable to guarantee fast printing rates, a reduced polymerization threshold, and finally fabricated structures with a high resolution . An efficient 2PI should have large two‐photon absorption (2PA) to ensure efficient photon absorption, and an efficient initiation mechanism, through which the absorbed energy can be efficiently used to generate active initiation species .…”
Section: Methodsmentioning
confidence: 99%
“…The σ 2PA of the photoinitiators were measured by z-scan technique, and the experimental setup has been described earlier [27]. Rhodamine B was used as reference to verify the reliability of the experimental setup.…”
Section: Two-photon Cross Section Measurementsmentioning
confidence: 99%
“…In this paper, four bifunctional photocleavable PIs comprising oxime‐ester moieties and conjugated carbazoles were designed and synthesized. We have shown that the conjugated carbazoles are good visible light chromophores and have excellent two‐photon sensitivity . Therefore, introduction of oxime‐ester moieties as latent initiation functionalities into the conjugated carbazole skeleton should provide efficient PIs sensitive to visible and near‐infrared light.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that the conjugated carbazoles are good visible light chromophores and have excellent two-photon sensitivity. [29] Therefore, introduction of oxime-ester moieties as latent initiation functionalities into the conjugated carbazole skeleton should provide efficient PIs sensitive to visible and near-infrared light. The effect of different substitution positions (4 a and 4 c) on the structureproperty relationship and the impact of different types of radials (4 c and 4 d) on the photoinitiating behavior ( Figure 1) were systematically studied.…”
Section: Introductionmentioning
confidence: 99%